2016
DOI: 10.3390/technologies4020017
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Plenoptic Imaging With Entangled Photons

Abstract: Plenoptic imaging is a novel optical technique for three-dimensional imaging in a single shot. It is enabled by the simultaneous measurement of both the location and the propagation direction of light in a given scene. In the standard approach, the maximum spatial and angular resolutions are inversely proportional, and so are the resolution and the maximum achievable depth of focus of the 3D image. We have recently proposed a method to overcome such fundamental limits by combining plenoptic imaging with an int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…Correlation plenoptic imaging (CPI) has recently been proposed for overcoming this fundamental limit [20]. The main idea is to exploit the second-order spatio-temporal correlation properties of light to perform spatial and directional detection on two distinct sensors: Using correlated beams [20][21][22], high-resolution "ghost" imaging is performed on one sensor [23][24][25][26][27] while simultaneously obtaining the angular information on the second sensor. As a result, the relation between the spatial (N x ) and the angular (N u ) pixels per line, at fixed N tot , becomes linear: N x + N u = N tot [20].In this paper, we present the first experimental realization of CPI.…”
mentioning
confidence: 99%
“…Correlation plenoptic imaging (CPI) has recently been proposed for overcoming this fundamental limit [20]. The main idea is to exploit the second-order spatio-temporal correlation properties of light to perform spatial and directional detection on two distinct sensors: Using correlated beams [20][21][22], high-resolution "ghost" imaging is performed on one sensor [23][24][25][26][27] while simultaneously obtaining the angular information on the second sensor. As a result, the relation between the spatial (N x ) and the angular (N u ) pixels per line, at fixed N tot , becomes linear: N x + N u = N tot [20].In this paper, we present the first experimental realization of CPI.…”
mentioning
confidence: 99%
“…By illuminating an object with an SPDC signal beam and detecting correlations between the momentum of the idler photons (defined by the transverse position of the single-mode detector) and the positions of the correlated signal photons (after the object) one can, in principle, record a complete Fourier ptychographic reconstruction without changing the illumination of the object. A proposal to harness EPR-like correlations in a similar way was recently proposed in the context of plenoptic imaging 29 .…”
Section: Resultsmentioning
confidence: 99%
“…We have theoretically shown that CPI can be achieved by exploiting the correlation properties of both chaotic light [39,40] and entangled photons from spontaneous parametric down-conversion (SPDC) [41]. We have also performed the first experimental proof of CPI with chaotic light [42], and we are currently generalizing the experimental demonstration to entangled photons.…”
Section: Introductionmentioning
confidence: 94%